Lessons after the early management of the COVID-19 outbreak in a pediatric transplant and hemato-oncology center embedded within a COVID-19 dedicated hospital in Lombardia, Italy. Estote parati - Balduzzi, Adriana (Bone Marrow Transplant, 2020)
Italy is the second exposed country worldwide, after China, and Lombardia is the most affected region in Italy, with more than half of the national cases, with 13% of whom being healthcare professionals. The Clinica Pediatrica Università degli Studi di Milano Bicocca is a general pediatric and hematology oncology and transplant center embedded within the designated COVID-19 general Hospital San Gerardo in Monza, located in Lombardia, Italy. Preventive and control measures specifically undertaken to cope with the emergency within hemato-oncology, transplant, and outpatient unit in the pediatric department have been described. Preliminary COVID-19 experiences with the first Italian pediatric hemato-oncology patients are reported. The few available data regarding pediatrics and specifically hemato-oncological patients are discussed. The purpose of this report is to share pediatric hemato-oncology issues encountered in the first few weeks of the COVID-19 outbreak in Italy and to alert healthcare professionals worldwide to be prepared accordingly.